The Nexus Between Electricity Consumption And Output In Malaysia: Evidence From Panel Data Analysis - Dzul Hadzwan, Husaini; Chin, Hong Puah; Hooi, Hooi Lean (IJAS, 2015)
This paper examines the relationship between electricity and output in Malaysia. We employ panel data analysis to seek concrete evidence in exploring the relationship between electricity consumption and output. We use panel data for 3 economic divisions in Malaysia, namely Peninsular Malaysia, Sabah and Sarawak for the period 2000-2013. We found that the bidirectional relationship between electricity consumption and output exists. In addition, electricity consumption and output have positive relationships. According to ceteris paribus assumption, we can say that at 1% increase of electricity consumption, it will cause a 0.71% increase of output growth. On the other hand, for every 1% increases of output growth, it causes a 1.41% increase of electricity consumption. Comparatively, the output growth causes much impact to the electricity consumption rather than the electricity consumption causes the output growth. In sum, we can say that electricity consumption is not driving much to output growth. However, an additional output produced requires much electricity in input production. Thus, our empirical result suggests that the efficiency of electricity usage needs to be improved to ensure an increase of electricity consumption is able to translate rapid output growth in Malaysia.